INGLIZ ANTROPONIMLARI VA ULARNING LINGVOMADANIY LUGATLARDA BERILISHI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article is devoted to the process of development of English anthroponyms. The article examines English personal names by period and emphasizes their connection with social conditions, environment, process, society, culture in each period. The role of fiction in the development of anthroponyms was also discussed. Linguistic and cultural dictionaries analyze naming, phonetic transcription and cultural information.